High‐dimensional immune profiles correlate with phenotypes of peanut allergy during food‐allergic reactions. Issue 4 (24th June 2022) - Klueber, Julia; Czolk, Rebecca; Codreanu‐Morel, Françoise; Montamat, Guillem; Revets, Dominique; Konstantinou, Maria; Cosma, Antonio; Hunewald, Oliver; Skov, Per Stahl; Ammerlaan, Wim; Hilger, Christiane; Bindslev‐Jensen, Carsten; et al.
Abstract: Background: Food challenges carry a burden of safety, effort and resources. Clinical reactivity and presentation, such as thresholds and symptoms, are considered challenging to predict ex vivo. Aims: To identify changes of peripheral immune signatures during oral food challenges (OFC) that correlate with the clinical outcome in patients with peanut allergy (PA). Methods: Children with a positive (OFC +, n = 16) or a negative (OFC −, n = 10) OFC‐outcome were included (controls, n = 7). Single‐cell mass cytometry/unsupervised analysis allowed unbiased immunophenotyping during OFC. Results: Peripheral immune profiles correlated with OFC outcome. OFC + ‐profiles revealed mainly decreased Th2 cells, memory Treg and activated NK cells, which had an increased homing marker expression signifying immune cell migration into effector tissues along with symptom onset. OFC − ‐profiles had also signs of ongoing inflammation, but with a signature of a controlled response, lacking homing marker expression and featuring a concomitant increase of Th2‐shifted CD4 + T cells and Treg cells. Low versus high threshold reactivity‐groups had differential frequencies of intermediate monocytes and myeloid dendritic cells at baseline. Low threshold was associated with increased CD8 + T cells and reduced memory cells (central memory [CM] CD4 + [Th2] T cells, CM CD8 + T cells, Treg). Immune signatures also discriminated patients with preferential skin versus gastrointestinal symptoms, whereby skin signs correlated with increased expression of CCR4, a molecule enabling skin trafficking, on various immune cell types. Conclusion: We showed that peripheral immune signatures reflected dynamics of clinical outcome during OFC with peanut. Those immune alterations hold promise as a basis for predictive OFC biomarker discovery to monitor disease outcome and therapy of PA. Abstract : Changes of peripheral immune profiles through oral food challenge‐course distinguish negative from positive outcome based on T helper cell (Th)2/non‐Th2 phenotypes. Symptom development correlates with inflammatory immune cell decrease and tissue migration characterized by homing marker expression. Discriminatory immune signatures reflect clinical endotypes of threshold dose reactivity and organ involvement.Abbreviations: GigaSOM, computational analysis tool for unsupervised clustering and dimension reduction; NK, natural killer cell; OFC, oral food challenge; Th, T helper cell; Treg, regulatory T cell